Salivary interleukin-17 and tumor necrosis factor-α in relation to periodontitis and glycemic status in type 2 diabetes mellitus - Gürsoy, Ulvi Kahraman; Yildiz Çiftlikli, Sinem; Könönen, Eija; Gürsoy, Mervi; Doğan, Başak (Journal of diabetes, 2015)
Background Poorly‐controlled glycemic status in type 2 diabetes mellitus (T2DM) is suggested to play a role in the periodontal inflammatory process by aggregating the local cytokine response. Our objectives were to profile salivary interleukin (IL)‐17 and tumor necrosis factor (TNF)‐α levels in subjects with T2DM and to examine their relevance for the periodontal health status and glycemic control levels. Methods Unstimulated whole saliva samples, together with full‐mouth periodontal recordings (plaque index [PI], bleeding on probing [BOP %], gingival index [GI], probing pocket depth [PPD], and clinical attachment level [CAL]), were collected from 123 subjects with T2DM. Additionally, demographic and general health parameters, including fasting blood glucose, glycated hemoglobin (HbA1c), were collected. Salivary IL‐17 and TNF‐α concentrations were analyzed using the Luminex®‐xMAP™ technique. Results Subjects with poorly‐controlled T2DM (HbA1c ≥ 7) had elevated serum triglyceride (P < 0.001) concentration as well as elevated scores of BOP % (P = 0.014), PI (P = 0.048), GI (P = 0.033), and CAL (P = 0.003) in comparison to those of well‐controlled T2DM (HbA1c < 7). When the subjects with detectable salivary IL‐17 were categorized in tertiles, the scores of PPD and BOP%, and salivary TNF‐α concentrations were significantly elevated in the highest (P = 0.007, P = 0.002 and P < 0.001, respectively) and middle (P = 0.052, P = 0.022, and P = 0.003, respectively) tertiles compared to subjects with non‐detectable salivary IL‐17. The adjusted association between PPD measurements and salivary IL‐17 concentrations was significant (P = 0.008). Conclusions Poorly‐controlled glycemic status relates to the severity of periodontal disease in T2DM. The association between PPD and IL‐17 in saliva, however, is independent from the effect of glycemic status. 摘要 背景： 目前认为血糖水平控制不佳在2型糖尿病（T2DM）患者牙周炎症发生过程中对聚集局部细胞因子反应有影响。我们的目的是描述T2DM受试者唾液中的白细胞介素（IL）‐17以及肿瘤坏死因子（TNF）‐α的水平，调查它们与牙周健康状态以及血糖控制水平之间的相关性。 方法： 从123名T2DM受试者中收集非刺激性的全唾液样本以及全口腔牙周记录（菌斑指数[plaque index，PI]，探查时出血[bleeding on probing，BOP %]，牙龈指数[gingival index，GI]，探测袋深度[probing pocket depth，PPD]以及临床附着水平[clinical attachment level，CAL]）。另外，还收集了人口统计学以及一般的健康指标，包括空腹血糖与糖化血红蛋白（HbA1c）。使用Luminex®‐xMAP™技术来分析唾液中的IL‐17与TNF‐α浓度。 结果： 与血糖控制良好的T2DM受试者（HbA1c < 7）相比，血糖控制不佳的T2DM受试者（HbA1c ≥ 7）血清中的甘油三酯浓度升高（P < 0.001），除此之外BOP %（P = 0.014）、PI（P = 0.048）、GI（P = 0.033）以及CAL（P = 0.003）的评分也更高。与唾液中检测不到IL‐17的受试者相比较，唾液中可检测到IL‐17的受试者按照IL‐17浓度三等分为3组，发现PPD与BOP %评分以及唾液中的TNF‐α浓度在浓度最高组（分别P = 0.007，P = 0.002与P < 0.001）与中间组（分别P = 0.052，P = 0.022与P = 0.003）都显著升高。经过校正之后发现PPD测量结果与唾液中的TNF‐α浓度具有显著相关性（P = 0.008）。 结论： T2DM患者血糖水平控制不佳与牙周病的严重程度相关。PPD与唾液中的IL‐17相关，然而，这种相关性独立于血糖状态的影响。